Intramedullary spinal cord metastasis from prostate carcinoma: a case report - Lieberson Robert E (Journal of Medical Case Reports, 2012)
Abstract Introduction Although vertebral and epidural metastases are common, intradural metastases and intramedullary spinal cord metastases are rare. The indications for the treatment of intramedullary spinal cord metastases remain controversial. We present the first biopsy-proven case of an intramedullary spinal cord metastasis from adenocarcinoma of the prostate. Case presentation Our patient was a 68-year-old right-handed Caucasian man with a Gleason grade 4 + 3 prostate adenocarcinoma who had previously undergone a prostatectomy, androgen blockade and transurethral debulking. He presented with new-onset saddle anesthesia and fecal incontinence. Magnetic resonance imaging demonstrated a spindle-shaped intramedullary lesion of the conus medullaris. Our patient underwent decompression and an excisional biopsy; the lesion’s pathology was consistent with metastatic adenocarcinoma of the prostate. Postoperatively, our patient received CyberKnife® radiosurgery to the resection cavity at a marginal dose of 27Gy to the 85% isodose line. At three months follow-up, our patient remains neurologically stable with no new deficits or lesions. Conclusions We review the literature and discuss the indications for surgery and radiosurgery for intramedullary spinal cord metastases. We also report the novel use of stereotactic radiosurgery to sterilize the resection cavity following an excisional biopsy of the metastasis.